Pudendal nerve block in feline perineal urethrostomy: Case report - Araújo, Alessandro Mendes; Zanoni, Fernando Luiz; Paes de Souza, Sabrina (Pubvet, 2023)
Due to the frequency of male felines suffering from recurrent urethral obstructions, perineal urethrostomy surgery appears to be a viable treatment for permanent unclogging of the urethra. The following work aims to report a case of utilizing locoregional block of the pudendal nerve as a means to provide regional analgesia for feline perineal urethrostomy surgery associated with penectomy. The patient was premedicated with Methadone 0.15 mg/kg and Acepromazine 0.01 mg/kg, induced with propofol 3mg/kg and Ketamine 1.5mg/kg, and anesthesia was maintained with Isoflurane. No severe changes in physiological parameters were seen during the trans-surgical period, and the patient had a quick recovery without showing pain or behavioral changes, proving the effectiveness of this block as a crucial analgesic tool in surgery.
Keywords: local anesthesia; surgery; feline; urethrostomy